Distribution system analysis and automation - Gers, Juan M. (London, United Kingdom The Institution of Engineering and Technology, 2013)
The following topics are dealt with: smart grid; distribution automation functions; short circuit calculation; reliability; volt/VAR control; harmonic analysis; power distribution protection and interoperability concepts.
Electronic reproduction.
Keywords: Smart power grids; Electric networks; Electric networks -- Computer programs; Electric power distribution; Electric power distribution -- High tension -- Computer programs; Electric power systems; Electric power systems -- Control; Electric power systems -- Protection; Electric power systems -- Reliability; Electric power transmission; Harmonic analysis; Harmonics; System theory; Electronic books